1996
DOI: 10.1093/oxfordjournals.ndt.a027209
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of ANCA in patients with ulcerative colitis necessarily imply renal involvement?

Abstract: Renal damage was not observed in ANCA-positive patients with ulcerative colitis even after 1 year of follow-up, suggesting that the ANCA found in these patients do not share the antigenic targets with the ANCA commonly found in renal vasculitis. Therefore the potential of ANCA of inducing renal lesions (if any) is dependent on their own antigenic specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This case challenges the view that ANCA in UC is not clinically relevant [5,9]. It is important to determine the antigenic specificity of ANCA rather than rely on immunofluorescence analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This case challenges the view that ANCA in UC is not clinically relevant [5,9]. It is important to determine the antigenic specificity of ANCA rather than rely on immunofluorescence analysis.…”
Section: Discussionmentioning
confidence: 97%
“…In one study of 50 patients with UC, 54% were shown to be either p-ANCA or c-ANCA positive but none of these antibodies reacted with PR3 or MPO [4]. In another study, ANCA-positive patients with UC were followed for a year during which no evidence of glomerulonephritis was found [5]. The authors concluded that ANCA found in UC are different to those associated with vasculitis, noting that none of the study patients had ANCA specific for PR3 or MPO.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gionchetti et al [20] reported that ANCAs are unlikely to contribute to the pathogenesis of UC. Rosa et al [21] reported that renal damage was not observed in ANCA-positive patients with UC even after 1 year of follow-up. In the present study, we did not fi nd a relation between ANCA titers and urinary albumin excretion (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies are not usually considered to carry potential for the development of systemic vasculitis as they lack specificity for Proteinase 3 (PR3) or Myeloperoxidase (MPO). ANCA-positive patients with UC were followed for a year during which no evidence of GN was found [14].…”
Section: Gr Up Smmentioning
confidence: 99%